Analisis Peran Komunikasi Interpersonal Orang Tua dalam Mengontrol Paparan Konten Brainrot Anomali pada Anak Usia Sekolah Dasar - Anindita Putri Ardianti; Livia Natasha; Deswinta Maharani Febiand; Rosalia Prismarini (KAMPUS AKADEMIK PUBLISING, 2026)
The rapid development of digital media has made it easier for children to access various types of content on social media, including brainrot anomaly content, which is often absurd, repetitive, and lacks educational value. This study aims to analyze the role of parental interpersonal communication in controlling children's exposure to brainrot anomaly content. This research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The participants consisted of three parents, one school counselor, and one elementary school-aged child. The findings indicate that interpersonal communication plays a significant role in controlling children's exposure through parental supervision, screen time limitation, discussions about digital content, and guidance in selecting age-appropriate media. Furthermore, collaboration between parents and schools is essential to improve children's digital literacy and encourage responsible digital media use.